DETERMINANTS OF DIGITAL MARKETING SUCCESS IN SMES: A SYSTEMATIC LITERATURE REVIEW - Elvina Elvina (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
This study aims to identify and synthesize the determinants of digital marketing success in Small and Medium Enterprises (SMEs) using a Systematic Literature Review (SLR) approach. The review followed PRISMA guidelines and analyzed articles retrieved from Scopus, Web of Science, Google Scholar, and Garuda databases published between 2011 and 2025. The findings indicate that digital marketing success in SMEs is driven by the interaction of technological, organizational, human resource, and external environmental factors. The effective use of social media, e-commerce, and digital platforms enhances SME performance and competitiveness when supported by integrated marketing strategies, digital competencies, and managerial support. This study contributes to the theoretical understanding of SME digital marketing and provides practical insights for practitioners and policymakers.